ANALISIS PENGARUH BID-ASK SPREAD, MARKET VALUE DAN VARIANCE RETURN TERHADAP HOLDING PERIOD SAHAM SEKTOR PERTAMBANGAN - Novita Selvia Perangin-angin; Fauzie Syarief (Ekonomi dan Keuangan, 2013)
ABSTRACT The formulation of the problem is to know the influence of bid-ask spread, market value and variance return on stock holding period  in  mining  sector.  The  objective of this research to analyze the influence of bid-ask spread, market value and variance return on stock holding period  in  mining  sector.          The data used were 10 companies selected  using purposive sampling technique with the criteria (1) The companies  in  mining  sector  registered  in Jakarta Exchange. (2) The companies which  were actively  consistent  during in the period 2009 up to 2011 in Jakarta Exchange. (3) The companies  fulfilling the indicator of  dependent  and  independent variables  during in the period 2009  up to 2011.  The data to analyze in  this research  were  panel data  using  Multiple  Linier Regression with Fixed Effect Model (FEM) in accordance with this model  having  the intercept  equation  and it was  not constant or with  difference on every   individual. Before analyzing the  data,  it was tested  firstly with Normality test and Hausman test to know  the  normality of data  and  to know  which  method  is appropriate  with fixed effect model in this research.  Further,  data  processing was done using Eviews 7 program.The results of research  showed that simultaneously through f-statistic  test  the variable of bid-ask spread, market value and variance return  had significant  influence to stock holding period in mining sector on significance rate 95%,whereas based on t-statistic test, it can be concluded that the variable of bid-ask spread and market value  had  positive  influence and  insignificant  influence to  stock holding period in mining sector and variance return with negative significant to stock holding period of mining sector  in period of 2009 up to 2011 with significance rate 95%. In addition, the coefficient of  determination  showed that  the variable of bid-ask spread, market value, and variance return  are capable  only  to explain that the  variable of stock holding period in mining sector  for 65.15%. Keywords: Stock Holding Period, Bid-Ask Spread, Market Value and Variance Return.